A rapid and sensitive liquid chromatography-tandem mass spectrometric method for the determination of hederasaponin B in rat plasma: Application to a pharmacokinetic study - Jiaxin Liu; Xueyan Yang; Lin Li; Qili Zhang; Zhaoyan Zhang; Xin Zhang; Yunli Zhao; Miao Yu; Zhiguo Yu (Elsevier, 2017)
A rapid, simple and sensitive ultra-high performance liquid chromatography-tandem mass spectrometric (UPLC-MS/MS) method was developed and validated for the determination of hederasaponin B, an active triterpenoid saponin widely existed in Hedera helix L. Plasma samples were processed by protein precipitation with acetonitrile and separated on a Thermo Hypersil GOLD C18 (2.1 mm × 50 mm,1.9 µm) at flow rate of 0.3 ml/min, with a gradient elution consisting of acetonitrile and water containing 0.1% (v/v) formic acid at 30 °C and detected by electrospray ionization mass spectrometry in the positive multiple reaction monitoring (MRM) mode. The linearity was found to be within the concentration range of 0.5-5000 ng/ml with a lower limit of quantification of 0.5 ng/ml. The absolute oral bioavailability of hederasaponin B was 0.24 ± 0.49%. This indicated that the concentration-time course of the hederasaponin B existed a double-peak phenomenon. This method was further applied to the determination of hederasaponin B in rat plasma and showed good practicability, for the first time, after intragastric (25 mg/kg) and intravenous (2 mg/kg) administration in rats.